Analisis Penerapan Strategi Pemasaran Produk Tabungan Easy Wadiah - Sheilamida Nanda Muhaeni; Phatriakalista Intan Apsari; Moh. Yusron; Arin Setiyowati (Universitas Muhammadiyah Ponorogo, 2022)
This research is the result of a qualitative research that aims to explain and analyze the Marketing Strategy of Easy Wadiah Savings Products BSI KCP Rungkut 1 Surabaya. This research includes Field Research where the author examines directly in the field to collect the data he wants to find. The data sources used are primary data and secondary data. Data collection techniques were carried out by observation, interviews, and literature studies. The results obtained are that Wadiah is a deposit from one party to another, both individuals and legal entities that must be guarded and returned whenever the depositor wants it. This paper also explains the tariffs and costs of the Easy Wadiah Savings product at Indonesian Islamic Bank KCP Rungkut 1 Surabaya and the marketing strategies used to market the Easy Wadiah Savings product. From the results of this study, the advice that can be given is that BSI KCP Rungkut 1 Surabaya can introduce BSI products, especially the Easy Wadiah Savings product to the public and its advantages are as wide as possible by increasing promotion through social media and BSI in the future can further improve quality, one of which is improving service. maximum capacity, more complete facilities and infrastructure, more stable management so that BSI vision and mission can be achieved